2008
DOI: 10.1021/ic800934h
|View full text |Cite
|
Sign up to set email alerts
|

Formation of P−C Bonds under Unexpectedly Mild Conditions. Phosphoryl Migration and Metal Coordination of Diphenylphosphinomethyl-oxazolines and -thiazolines

Abstract: The heterocycles 2-methyl-2-oxazoline (mox) and 2-methyl-2-thiazoline (mth) react with Ph2PCl under mild conditions, in the presence of NEt3 which promotes their phosphorylation by stabilization of their enamino tautomers mox(e) and mth(e), respectively, and which also behaves as HCl scavenger. Depending on the reaction conditions, three different phosphine ligands were obtained in good yields from mox: the monophosphine Ph2PCH2C=NCH2CH2O (1ox) and the isomeric diphosphines Ph2PCH=COCH2CH2NPPh2 (2ox) (X-ray st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…3 The coordination behavior of 2-{bis(diphenylphosphino)-methyl}oxazoline, (Ph 2 P) 2 CHCNCH 2 CH 2 O (1) (Scheme 1), has barely been examined. 4 Comparative studies performed with 2-{bis(diphenylphosphino)methyl}pyridine, (Ph 2 P) 2 CH(2-C 5 H 4 N), could shed light on the possible influence of the different basicities of the N-heterocycles on the chemistry and properties of their metal complexes. Various coordination modes have been evidenced for this ligand, with κ 2 -P,P, κ 2 -P,N, or κ 3 -N,P,P bonding in mononuclear complexes 7,8 and μ-κ 2 -P,P or μ-κ 1 -P:κ 2 -P,N bonding modes in dinuclear complexes.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The coordination behavior of 2-{bis(diphenylphosphino)-methyl}oxazoline, (Ph 2 P) 2 CHCNCH 2 CH 2 O (1) (Scheme 1), has barely been examined. 4 Comparative studies performed with 2-{bis(diphenylphosphino)methyl}pyridine, (Ph 2 P) 2 CH(2-C 5 H 4 N), could shed light on the possible influence of the different basicities of the N-heterocycles on the chemistry and properties of their metal complexes. Various coordination modes have been evidenced for this ligand, with κ 2 -P,P, κ 2 -P,N, or κ 3 -N,P,P bonding in mononuclear complexes 7,8 and μ-κ 2 -P,P or μ-κ 1 -P:κ 2 -P,N bonding modes in dinuclear complexes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…3 were readily protonated in the solid state by HBF 4 2+ also forms upon reaction of 1 with [PtCl 2 (NCPh) 2 ] in MeCN or CH 2 Cl 2 . 3 In 3a and 3b, ligand 1′ has a protonated heterocyclic nitrogen (Scheme 9), in contrast to its tautomer 1, which is the only form of the uncoordinated ligand that has been isolated and observed spectroscopically.…”
Section: ■ Introductionmentioning
confidence: 99%
“…125 A range of new phosphines (87)- (89) has been prepared via the reactions of 2-methyl-2-oxazoline and 2-methyl-2-thiazoline with chlorodiphenylphosphine under unexpectedly mild conditions. 126 The reaction of formamidino-functionalised thiazoles with bromophosphines in the presence of pyridine, followed by methanolysis of the formamidino group, provides a very straightforward and efficient route to the thiazolylphosphines (90), useful ligands for the copper-catalysed arylation and vinylation of nucleophiles. 127 A direct, mild and efficient method for the trifluoromethylation of primary and secondary phosphines has been developed using readily accessible and inexpensive hypervalent iodine(III)-CF 3 reagents.…”
Section: Bhmentioning
confidence: 99%
“…Chelating P , N ligands and their metal complexes continue to attract much interest owing to their intrinsic properties and numerous applications . We recently found that unusual molecular rearrangements involving P−C and P−N bond formation/breaking can occur during the synthesis of the phosphine ligands (2-oxazoline-2-ylmethyl)diphenylphosphine ( L ox ) and (2-thiazoline-2-ylmethyl)diphenylphosphine ( L th ) . These ligands readily form a number of transition metal complexes .…”
Section: Introductionmentioning
confidence: 99%